Dynamic Modelling of 3-RUS Spatial Parallel Robot Manipulator - Quang, Nguyen Hong; Quyen, Nguyen Van; Hai, Do Trung; Hien, Nguyen Nhu (Review of Computer Engineering Research, 2020)
Parallel manipulators are characterized as having closed-loop kinematic chains. Parallel robots have received increasing attention due to their inherent advantages over conventional serial mechanism, such as high rigidity, high load capacity, high velocity, and high precision. A definite advantage of parallel robots is the fact that, in most cases, actuators can be placed on the truss, thus achieving a limited weight for the moving parts, which makes it possible for parallel robots to move at a high speed. These advantages avoid the drawbacks on serial ones and make the mobile platforms of the parallel manipulators carry out higher performances. Therefore, parallel manipulators have been applied to the industrial manufacturing, flight simulation, medical resuscitation, and so on. The basis for model-based control of parallel manipulators is an efficient formulation of the motion equations. In this paper a formulation of the motion equations in redundant coordinates is presented for parallel manipulators. The fully coupled non-linear equations of motion of 3-RUS spatial parallel manipulator having 3 DOF with Revolute-Universal-Spherical joints are obtained by using the Lagrange equations with multipliers for constrained multibody systems.